Identification of Coliform bacteria content in ‘Thai Tea' drinks and its correlation with hygiene factors in Yogyakarta, Indonesia - Suryani, Dyah; Sunarti, Sunarti; Safitri, Rosyida Awali; Khofifah, Hesti; suyitno, Suyitno (YCAB Publisher & IAKMI SULTRA, 2021)
Background: Various water-borne diseases have been seen in developed and developing countries, like Coliform bacteria in food and drink due to their poor making.Objective: This study aims to estimate the hygiene factors and examine the content of Coliform bacteria and in Thai Tea drinks in Yogyakarta Municipality.Methods: A cross-sectional method was used in all Thai Tea product sellers in Yogyakarta Municipality from September to November 2020. A total of 30 sellers were included, and 30 different types of Thai Tea products were tested using the Most Probably Number (MPN) method at the Health and Calibration Laboratory Center, Yogyakarta, Indonesia. Descriptive statistics, Chi-square, and Fisher exact test were used for data analysis.Results: Laboratory tests showed half of Thai Tea products contaminated with Coliform bacteria more than MPN/100ML. Of all Thai Tea sellers, about 83.3% of them were never hygiene food sanitation training. Findings also show that the seller's hygiene sanitation was significantly associated with the existence of Coliform bacteria in Thai Tea (Crude OR=0.44, 95% CI=0.20-0.98). The sellers with poor sanitation facilities were four times more likely to have Coliform bacteria in their Thai Tea products (Crude OR=4.0, 95% CI=1.41-11.35). Meanwhile, hygiene food sanitation training and location of selling did not have a significant relationship with the presence of Coliform in Thai Tea.Conclusion: In sum, the existence of Coliform in Thai Tea drinks in the city of Yogyakarta is influenced by the hygiene sanitation and sanitation facility. Training on personal hygiene for each seller is necessary to obtain Thai Tea products that contain Coliform bacteria according to standards. This is very useful to do to reduce food-borne disease. This study was funded by Ahmad Dahlan University, Yogyakarta, Indonesia.